Coordination in interpersonal systems. Issue 8 (17th November 2022) - Butler, Emily A.
ABSTRACT: Coordinated group behaviour can result in conflict or social cohesion. Thus having a better understanding of coordination in social groups could help us tackle some of our most challenging social problems. Historically, the most common way to study group behaviour is to break it down into sub-processes, such as cognition and emotion, then ideally manipulate them in a social context in order to predict some behaviour such as liking versus distrusting a target person. This approach has gotten us partway to understanding many important collective behaviours, but I argue that making major changes in the world will require a more integrated approach. In this review, I introduce dynamic systems theory, with a focus on interpersonal systems, where all the processes we typically study in individuals, such as cognition and emotion, become intertwined between social partners over time. I focus on the concept of coordination, defined as a temporal correlation between interacting components of a system (or systems) arising due to coupling between them. Finally, I show how this perspective could be used to guide investigations of social problems such as polarisation.